2017
DOI: 10.19082/5663
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of intra-articular prolotherapy versus peri-articular prolotherapy on pain reduction and improving function in patients with knee osteoarthritis: A randomized clinical trial

Abstract: BackgroundOsteoarthritis is a common degenerative disease. Prolotherapy is an alternative therapy used in multiple musculoskeletal disorders.ObjectiveTo compare the effectiveness of intra-articular dextrose injection versus peri-articular prolotherapy in patients with knee osteoarthritis (KOA).MethodsFifty-two adults with painful primary knee osteoarthritis for at least three months were randomized to intra- and peri-articular injection groups. Prolotherapy was done twice with two week intervals. The outcome m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…Other studies have reported similar reduction of pain and function improvement when comparing intra-articular hypertrophic dextrose vs subcutaneous dextrose; [24,25] this therapeutic effect cannot be attributed to chondrogenic mechanisms or to ligamentous or tendinous remodeling, but perhaps due to neurogenic effects. Two studies [19,20] combined intra-articular and extra-articular HDP applications on ligaments insertions and tendons and observed a long term effect.…”
Section: Therapeutic Efficacymentioning
confidence: 73%
See 4 more Smart Citations
“…Other studies have reported similar reduction of pain and function improvement when comparing intra-articular hypertrophic dextrose vs subcutaneous dextrose; [24,25] this therapeutic effect cannot be attributed to chondrogenic mechanisms or to ligamentous or tendinous remodeling, but perhaps due to neurogenic effects. Two studies [19,20] combined intra-articular and extra-articular HDP applications on ligaments insertions and tendons and observed a long term effect.…”
Section: Therapeutic Efficacymentioning
confidence: 73%
“…Fortyeight studies were read in detail, then 38 were excluded for the following reasons: review studies (n = 20), other pathology interventions (n = 9), case series studies (n = 7), controlled clinical trials compared against non-interventional treatments (n = 2). Finally, 10 randomized clinical trials [17][18][19][20][21][22][23][24][25][26] were eligible for inclusion in this systematic review. The systematized flowchart search is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations